Extensive ICP-MS and HPLC-QQQ detections reveal the content characteristics of main metallic elements and polyphenols in the representative commercial tea on the market - An, Yanlin; Qiao, Dahe; Jing, Tingting; Li, Shize (Frontiers in Nutrition, 2024)
The content of polyphenols and metal elements in tea has an important impact on the choice of consumers. In this study, we conducted a comparative analysis of ten elements including Fe, Mg, Al, Zn, Cu, Mn, Ni, Cr, Pb, and As in 122 representative tea samples from 20 provinces. The results showed that the difference of metal content among six tea categories was greater than that among provinces, and the overall metal content of black tea was relatively higher. The contents of all elements from high to low were: Mg > Mn > Al > Fe > Zn > Cu > Ni > Cr > Pb > As. The contents of Ni, Fe, Al, Zn and Mn showed significant differences among multiple types of tea categories. While the detection rates of Pb and As were 10.7% and 24.6% respectively. The contents of all elements were in line with the national limit standards. Meanwhile, the relative contents of theanine, caffeine and a total of 53 polyphenolic compounds in 122 tea samples were detected. The analysis showed that the content of these compounds differed least between green and yellow tea, and the largest difference between black tea and oolong tea. This study provides important support for consumers to choose tea rationally.